2018
DOI: 10.2337/db17-0880
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Is Only Partly Required for the Glucagonostatic Effect of Glucose but Is Necessary for the Glucagonostatic Effect of KATP Channel Blockers

Abstract: The mechanisms of control of glucagon secretion are largely debated. In particular, the paracrine role of somatostatin (SST) is unclear. We studied its role in the control of glucagon secretion by glucose and K channel blockers, using perifused islets and the in situ perfused pancreas. The involvement of SST was evaluated by comparing glucagon release of control tissue or tissue without paracrine influence of SST (pertussis toxin-treated islets, or islets or pancreas from mice). We show that removal of the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 52 publications
(65 reference statements)
9
48
2
Order By: Relevance
“…To determine whether the reduced SST secretion explained the lack of inhibition of glucagon secretion by glucose, we compared [Ca 2+ ] i oscillatory activity in CTL and HFD mice before and after pharmacological inhibition of somatostatin signalling in the islet. Mouse alpha–cells express primarily SST receptor 2 (SSTR2; see [7] and [45]). We therefore inhibited SST signaling using the SSTR2 inhibitor CYN154806 (CYN) and measured [Ca 2+ ] i oscillation frequency.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the reduced SST secretion explained the lack of inhibition of glucagon secretion by glucose, we compared [Ca 2+ ] i oscillatory activity in CTL and HFD mice before and after pharmacological inhibition of somatostatin signalling in the islet. Mouse alpha–cells express primarily SST receptor 2 (SSTR2; see [7] and [45]). We therefore inhibited SST signaling using the SSTR2 inhibitor CYN154806 (CYN) and measured [Ca 2+ ] i oscillation frequency.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism(s) by which glucagon secretion is controlled is a contentious topic (Gylfe, 2013;Lai et al, 2018). Based on observations in isolated (ex vivo) islets, islets have been shown to respond to hypoglycaemia (and adjust glucagon secretion accordingly) via intrinsic (Rorsman et al, 2014;Basco et al, 2018;Yu et al, 2019) and paracrine mechanisms (Briant et al, 2018;Vergari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To address this critical point, we therefore investigated the potential effects of activation/blockage of intra‐islet SST and insulin signalling, as well as the ability of glucose to inhibit glucagon secretion, when insulin/SST signalling was prevented. Double‐immunofluorescence staining suggested that SSTR‐2 and ‐5 are the most often detected subtypes in mouse and rat alpha cells, 27 and in more recent studies in mice based on pre‐glucagon promoter driven expression of fluorescent proteins, enabling alpha cell identification and sorting, SSTR‐2, ‐3 and ‐5 were found to be the most abundantly expressed subtypes, whereas SSTR‐1 and ‐4 were not detected 10,28 . Unfortunately, we have not been able to find studies on SSTR‐1, ‐5 expression in rat islets, but based on the cited mouse expression data, we included a SSTR‐3 antagonist to a mixture of SSTR‐2 and ‐5 antagonists in order to eliminate potential SST‐signalling through these receptor subtypes.…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, there is data indicating that glucagon secretion from mouse and human islets is maximally inhibited already at 5‐7 mmol/L glucose, where insulin and SST secretion is usually not stimulated 3,22,23 . It is therefore unclear whether endogenous insulin or SST is involved in the physiological glucose regulation of glucagon secretion; indeed, some studies do not support this 10,12,23,24 . The primary aim of the present study was to re‐examine the role of insulin and co‐secreted GABA, as well as SST for glucose‐induced inhibition of glucagon secretion.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation